Associations between Life’s Essential 8 and liver function: a cross-sectional study - Liang, Qiaoli; Zou, Menglong; Peng, Ziming (Frontiers in Nutrition, 2025)
BackgroundLife’s Essential 8 (LE8) score, developed by the American Heart Association, assesses cardiovascular health using eight components: diet, physical activity, nicotine exposure, sleep health, body mass index, lipids, blood glucose, and blood pressure. Liver function is a critical indicator of overall health, with impairments linked to numerous chronic diseases. While the LE8 score has been extensively studied in relation to cardiovascular outcomes, its association with liver function remains underexplored. Understanding this relationship is crucial for integrating cardiovascular and hepatic health management, particularly given the shared metabolic pathways underlying these systems. This study aims to examine the relationship between LE8 scores and liver function indicators in a large cohort, addressing a critical gap in understanding the interplay between cardiovascular and liver health.MethodsData from the 2007–2018 National Health and Nutrition Examination Survey (NHANES) were used in this cross-sectional study. The study included 21,873 participants, stratified into low (0–49), moderate (50–79), and high (80–100) LE8 score categories. The relationship between LE8 scores and liver function markers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and ALT/AST ratio, was evaluated using multivariable linear regression, smoothed curve fitting, threshold effect analysis, and weighted quantile sum (WQS) regression. Subgroup analyses were performed based on sex and age to assess potential interactions.ResultsHigher LE8 scores were significantly associated with improved liver function, particularly highlighted by two major findings. First, nonlinear associations were observed between LE8 scores and liver function parameters, including ALT and ALT/AST ratio, with stronger effects beyond specific thresholds (ALT: 50.625, ALT/AST: 61.875). Second, subgroup analyses revealed that these associations were more pronounced in younger participants (<60 years), suggesting age-specific differences in the relationship. These age-related differences might be attributed to variations in metabolic function or differences in the severity of cardiovascular and liver-related risk factors between younger and older individuals. WQS regression identified body mass index, blood pressure, blood glucose, and nicotine exposure as the strongest contributors to liver function markers. These findings underscore the potential of LE8 scores as a comprehensive indicator for liver health, particularly in younger populations.ConclusionThis study suggests that LE8 scores is associated with improved liver function. Clinicians and public health practitioners could consider integrating LE8 scores into routine assessments to help identify individuals at risk for liver dysfunction, particularly among younger populations. Further research should explore whether interventions targeting cardiovascular health could also improve liver function outcomes.